2012
DOI: 10.1093/geront/gns142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Implementation of an Evidence-Based Program to Manage Concerns About Falls in Older Adults

Abstract: After implementation in home care organizations, the program reduced concerns about falls, avoidance behavior, and falls in community-living older adults. These findings are highly consistent with the outcomes of a previously performed randomized controlled trial, indicating that the program can be successfully implemented in practice. Further dissemination of the program is recommended to reduce concerns about falls and related activity avoidance in community-living older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
2
31
0
1
Order By: Relevance
“…8 A meta-analysis of nine studies examining t'ai chi in the management of fall prevention, fear of falling, and balance in older adults concluded that insufficient evidence existed to recommend such an intervention in this context. 19,20 A more recent randomised controlled study in 176 elders, randomised to one of three groups (intensive t'ai chi with cognitive-behavioural strategies, t'ai chi alone and a usual care control group) showed improvements in fear of falling as measured by the Falls Efficacy Scale 13 (FES) in the cognitive strategies group compared with the other two groups. 21 So, although t'ai chi can help to prevent falls in older adults, 22 its role specifically in the management of fear of falling is less clear.…”
Section: Falls and Fear Of Fallingmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A meta-analysis of nine studies examining t'ai chi in the management of fall prevention, fear of falling, and balance in older adults concluded that insufficient evidence existed to recommend such an intervention in this context. 19,20 A more recent randomised controlled study in 176 elders, randomised to one of three groups (intensive t'ai chi with cognitive-behavioural strategies, t'ai chi alone and a usual care control group) showed improvements in fear of falling as measured by the Falls Efficacy Scale 13 (FES) in the cognitive strategies group compared with the other two groups. 21 So, although t'ai chi can help to prevent falls in older adults, 22 its role specifically in the management of fear of falling is less clear.…”
Section: Falls and Fear Of Fallingmentioning
confidence: 99%
“…28 The study intervention was carefully developed and grounded in cognitive-behavioural theory, but interpretation of findings is hampered considerably by the lack of clarity on sample size calculation and outcome measures, and the absence of generic quality-of-life measures and measures of physical functioning. The same research group later reported a before-and-after design study 20 implementing a similar protocol into routine health care in 125 community-living older people, with significant improvements in concerns about falling.…”
Section: Psychological Treatments For Fear Of Fallingmentioning
confidence: 99%
“…A Matter of Balance: Managing Concerns about Falls (AMOB) is an evidence‐based programme for older adults that focuses on teaching cognitive behavioural strategies for managing fear related to falling and subsequent activity restrictions . Several studies have reported participant outcomes associated with implementation of the AMOB programme . Results indicated a positive impact on FOF, activity avoidance/restriction, falls self‐efficacy, balance confidence, and functional measures .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Netherlands has an adapted Dutch version of ‘A Matter of Balance’ [20, 21]. This multicomponent cognitive behavioural group programme has proven cost-effective in treating fear of falling and has been implemented nationally [2224]. Recently a home-based version of ‘A Matter of Balance’ was developed and this latter programme also proved (cost)effective in reducing fear of falling and associated activity restriction, disability and indoor falls [25, 26].…”
Section: Introductionmentioning
confidence: 99%